Modeling of liquid phase sintering and cohesive phase strength in iron ore and applications

CN117470611BActive Publication Date: 2026-10-30CENT SOUTH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311486094.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2026-10-30
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

[0004]专利一种粘结相粘结强度的方法ZL201910446992.3直观的测定了粘结相与铁矿之间的粘结强度,但是对于粘结相本身的强度判定缺乏考虑

Benefits of technology

[0024]1)本发明所提供的模型基于烧结相的成相原理以及正交方向上的力学峰值强度可以快速准确的得到烧结矿的宏观粘结强度,采用刚玉柱为粘结对象,避免了铁矿中不同成分液相同化基片对烧结强度产生的影响,保证了粘结相强度测定的结果更准确。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117470611B_ABST
    Figure CN117470611B_ABST
Patent Text Reader

Abstract

The application provides a model for liquid-phase sintering of iron ore and strength of a bonding phase and application thereof. The model accurately tests the macro mechanical strength of the bonding phase of sintered iron ore through two sets of destructive mechanical experiments in orthogonal directions, and greatly improves the accuracy of the determination result of the strength of the bonding phase by simulating the stress state of the bonding phase of sintered ore at different levels in the actual sintering process through the matching of the sintering temperature, time and gravity. The model provided by the application quantitatively detects the strength of the bonding phase of different sintered iron ores, fully considers the influence of the liquid-phase generation amount, liquid-phase fluidity and pressure of the upper material on the sintering process, and objectively evaluates the strength of the bonding phase, and has the advantages of wide applicability, convenient operation, high matching with the sintering of iron ore and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for testing the strength of the binder phase, specifically to a model and application of iron ore liquid-phase sintering and binder phase strength, belonging to the field of iron and steel metallurgical technology. Background Technology

[0002] In the context of dual-carbon production, concentrate production is a crucial link in low-carbon ironmaking, and sintering is an important part of concentrate production. Therefore, the properties of sinter directly affect whether the blast furnace achieves low carbon emissions. Sinter strength is an important physical property indicator, affecting not only the particle size distribution and reduction / pulverization properties of the sinter, but also the permeability and smooth operation of the blast furnace. Research on sinter strength suggests that it depends on the strength of the ore itself, the strength of the bonding interface, and the strength of the binder phase. It is generally believed that the ore's intrinsic strength is unchangeable; therefore, current research mainly focuses on the interfacial bonding strength and the strength of the binder phase.

[0003] In previous research, patent ZL201710234718.0 proposed a method for determining the strength of the binder phase. This method involves preparing a binder phase by mixing iron ore powder and CaO to form a mixture with a basicity of 3.0. Artificially pressed iron ore powder lumps are used as the substrate for liquid phase bonding. Shear force is applied to the formed binder phase to determine its strength. However, this method, which sets the basicity of the binder phase to 3.0, lacks relevance to the actual sintered binder phase. In actual sintering, the overall basicity is fixed, but the sintered mixture contains high-silica and low-silica ores. Therefore, for a specific iron ore, what is fixed is the CaO ratio, not the basicity. Furthermore, the main components forming the composite calcium ferrite, such as MgO and Al2O3, depend entirely on their amount in the iron ore, making it difficult to simulate the actual liquid phase. Most importantly, according to mineralization theory, the liquid phase sandwiched between iron ore particles will undergo assimilation reactions with the iron ore particles at both ends, thereby altering the composition of the liquid phase and leading to a significant difference between the actual and designed liquid phase compositions.

[0004] Patent ZL201910446992.3 describes a method for determining the bonding strength of a binder phase, which directly measures the bonding strength between the binder phase and the iron ore, but it lacks consideration for determining the strength of the binder phase itself.

[0005] In summary, current methods for studying the strength of the binder phase have certain shortcomings. Firstly, the bonding between the liquid phase and the iron ore substrate alters the composition of the liquid phase. Secondly, previous studies lacked sufficient understanding of the composition of the sintering liquid phase, primarily relying on methods based on basicity, which deviated from the actual composition of the liquid phase. Therefore, developing a convenient, reliable method for determining the strength of the binder phase that conforms to the actual sintering liquid phase is of great significance for studying iron ore sintering and the control of its liquid phase composition. Summary of the Invention

[0006] To address the problems existing in the prior art, the first objective of this invention is to provide a model for the liquid-phase sintering and binder phase strength of iron ore. This model, based on the sintering mineralization principle and the mechanical peak strength in the orthogonal direction, can quickly and accurately obtain the macroscopic binder strength of sintered ore. By using corundum pillars as the binder, the influence of the isomorphic substrate of different components in the liquid phase of iron ore on the sintering strength is avoided, ensuring that the results of the binder phase strength measurement are more accurate.

[0007] The second objective of this invention is to provide an application of a liquid-phase sintering and binder phase strength model for iron ore, used for quantitative detection of the strength of different sintered phases in iron ore. Based on the model provided by this invention, the strength of different sintered phases in iron ore is quantitatively detected, fully considering the influence of liquid phase generation, liquid phase fluidity, and pressure from the upper material during the actual sintering process. This improves the accuracy of binder phase strength test results from the perspectives of the nature and environment of the binder phase. Furthermore, accurate testing of the macroscopic mechanical strength of the sintered binder phase is achieved through orthogonal mechanical data.

[0008] To achieve the above technical objectives, this invention provides a model for the liquid-phase sintering of iron ore and the strength of the binder phase, characterized in that:

[0009] 1) The raw materials are mixed according to the proportions based on the sintered phase composition of iron ore and then pressed into test blocks;

[0010] 2) Place the sample block between two horizontal parallel corundum columns and heat and sinter it. After sintering, air cool it to room temperature to obtain the sample to be tested.

[0011] 3) Perform destructive mechanical testing on the sample to be tested, obtain the peak mechanical strength data and the sintered phase bonding area of ​​the sample to be tested, and calculate the strength of the bonding phase in the vertical direction;

[0012] 4) Place the test block between two vertical parallel corundum pillars and repeat steps 2) and 3) to obtain the horizontal bonding phase strength;

[0013] 5) Based on the vertical and horizontal liquid phase strengths, the final binder phase strength is obtained through fitting.

[0014] The sintered phase is the liquid phase generated during the sintering process of iron ore and flux.

[0015] As a preferred embodiment, the sintered phase of the iron ore is mainly composed of -3mm material in the raw material.

[0016] As a preferred embodiment, the raw material particle size is <200 mesh, and the pressure range for pressing the test block is 400–450 kg / cm². 2 .

[0017] As a preferred embodiment, the diameter of the test block is 3-15 mm and the weight is 0.05-0.5 g.

[0018] As a preferred embodiment, the corundum column has a weight range of 5–60g, a diameter range of 8–30mm, and a height range of 5–15mm.

[0019] As a preferred embodiment, the bonding area of ​​the sintered phase is determined by using the minimum bonding area on the two corundum pillars.

[0020] As a preferred embodiment, the sinter mainly comprises the following mass fraction components: 8-30 parts CaO, 1-4 parts MgO, 1-5 parts Al2O3, and 2-8 parts SiO2.

[0021] As a preferred embodiment, the heating and sintering conditions are as follows: heating rate of 5–15℃ / s, temperature of 1250–1350℃, high-temperature time ≤5min, and cooling rate of 30–100℃ / min. When simulating the performance of sintered ore in different areas of the sintering trolley, the weight of the corundum column, heating rate, maximum temperature, and high-temperature time should be adjusted accordingly. For example, when simulating surface sintered ore, the weight of the corundum column should be reduced, the temperature should be appropriately lowered, the high-temperature time shortened, and the cooling rate increased; when simulating lower sintered ore, the temperature should be increased accordingly, the high-temperature time extended, and the heating rate reduced.

[0022] This invention also provides an application of a model for the liquid-phase sintering and binder phase strength of iron ore, used for quantitative detection of the strength of different sintered phases of iron ore.

[0023] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are as follows:

[0024] 1) The model provided by this invention is based on the phase formation principle of sintered phase and the mechanical peak strength in the orthogonal direction, which can quickly and accurately obtain the macroscopic bonding strength of sintered ore. It uses corundum pillars as bonding objects, which avoids the influence of different liquid components in iron ore on the homogenization substrate on the sintering strength, and ensures that the results of the bonding phase strength measurement are more accurate.

[0025] 2) In the technical solution provided by the present invention, starting from the composition of the binder phase during the iron ore sintering process, the pressure state of sintered ore at different levels in the actual process is simulated by adjusting the weight of the corundum column, thereby improving the matching degree between the model and the actual sintering situation and accurately measuring the strength of the binder phase formed by the liquid phase that causes the bonding effect, which is more accurate than the strength of the binder phase measured by the incomplete melting.

[0026] 3) In the technical solution provided by the present invention, the strength of different iron ore sintering phases is quantitatively detected based on the above model. The influence of liquid phase generation, liquid mobile phase and upper material on the pressure during the actual sintering process is fully considered. The accuracy of the binder phase strength test results is improved from the nature and environment of the binder phase. Furthermore, the macroscopic mechanical strength of the sintering phase is accurately tested through orthogonal mechanical data. Attached Figure Description

[0027] Figure 1 This is a schematic diagram and a flowchart of the detection process for simulating longitudinal bonding according to the present invention;

[0028] Figure 2 This invention provides a schematic diagram and a flowchart of the detection process for simulating horizontal bonding. Detailed Implementation

[0029] The following embodiments are intended to further illustrate the present invention, but not to limit it. Table 1 shows the specific implementation conditions for each embodiment, and the corresponding implementation results are shown in Table 2.

[0030] Table 1 Basic conditions of the embodiments

[0031]

[0032] Table 2 Effects of each embodiment

[0033] 1 0.87 234 269 2 1.08 369 342 3 0.80 206 258 4 0.65 156 240 5 0.93 248 267 6 1.32 361 273 7 1.41 373 265 8 0.54 149 275 9 0.71 241 339 10 0.62 153 247 11 0.28 65 232

[0034] Example 1

[0035] The reference liquid phase composition of the sintered ore used in this embodiment was: CaO 18%, MgO 2.5%, Al2O3 2.0%, SiO2 5.5%, with the remainder being Fe2O3. Under the conditions of a sintering temperature of 1300℃ and a high-temperature time of 4 minutes, the longitudinal sintering liquid phase bonding strength was investigated, and the obtained liquid phase bonding area was 0.87 cm². 2 The strength of the binder phase is 269 N / cm. 2 .

[0036] Example 2

[0037] This embodiment is exactly the same as Embodiment 1, except that the CaO content in the sintering liquid phase is increased to 25%. The resulting sintering liquid phase has a bonding area increased to 1.08 cm². 2 The strength of the binder phase increased to 342 N / cm. 2 This indicates that increasing the CaO content in the sintering liquid phase not only promotes the fluidity (or wettability) of the liquid phase but also promotes the formation of a high-quality binder phase, thereby increasing the strength of the binder phase.

[0038] Example 3

[0039] This embodiment is exactly the same as Embodiment 1, except that the MgO content in the sintering liquid phase is increased to 3.0%. The resulting sintering liquid phase has a reduced bonding area of ​​0.80 cm². 2 The strength of the binder phase decreased to 258 N / cm. 2 This indicates that increasing the MgO content in the sintering liquid phase is detrimental to the flow of the liquid phase and reduces the strength of the binder phase.

[0040] Example 4

[0041] This embodiment is exactly the same as Embodiment 1, except that the Al2O3 content in the sintering liquid phase is increased to 3.0%. The resulting sintering liquid phase has a reduced bonding area of ​​0.65 cm². 2 The strength of the binder phase decreased to 240 N / cm. 2 It is evident that increasing the Al2O3 content in the liquid phase has a significant impact on the fluidity of the liquid phase, resulting in a significant reduction in the bonding area and a decrease in the strength of the bonding phase.

[0042] Example 5

[0043] This embodiment is identical to Embodiment 1, except that the weight of the corundum pillar is increased from 10g to 24g to simulate the effect of pressure changes during sintering. The resulting bond area of ​​the sintered liquid phase is increased to 0.90 cm². 2 The strength of the binder phase decreased to 267 N / cm. 2 Increasing the gravitational pressure during the sintering process can increase the bonding area of ​​the sintered liquid phase to some extent, but it has little effect on the strength of the bonding phase.

[0044] Example 6

[0045] This embodiment is exactly the same as Embodiment 1, except that the weight of the liquid masterbatch agglomerates is increased from 0.1g to 0.2g. The resulting sintered liquid phase has a bonding area of ​​1.32cm². 2 The strength of the binder phase increased to 273 N / cm. 2 Increasing the weight of the liquid masterbatch is equivalent to increasing the proportion of the sintering liquid phase, thus significantly increasing the bonding area of ​​the liquid phase, but the change in the strength of the bonding phase is relatively small.

[0046] Example 7

[0047] This embodiment is identical to Embodiment 6, except that the diameter of the liquid masterbatch agglomerates is increased from 8 mm to 10 mm. The resulting sintered liquid phase has a bonding area of ​​1.41 cm². 2 The strength of the binder phase is 265 N / cm. 2 Increasing the surface area of ​​the liquid phase masterbatch promotes the bonding range of the liquid phase, but the strength of the binder phase changes little or decreases slightly.

[0048] Example 8

[0049] This embodiment is exactly the same as Embodiment 1, except that Embodiment 1 characterizes the longitudinal strength, while this embodiment characterizes the horizontal strength. The bonding area of ​​the obtained sintered liquid phase is 0.54 cm². 2 The strength of the binder phase is 275 N / cm. 2 The results showed that the longitudinal bonding range was significantly reduced, but the bonding phase strength changed only slightly.

[0050] Example 9

[0051] This embodiment is identical to Embodiment 8, except that the CaO content in the liquid phase masterbatch is increased to 25%. The resulting sintered liquid phase has a bonding area of ​​0.71 cm². 2 The strength of the binder phase is 339 N / cm. 2 Compared to Example 8, increasing the CaO content not only promotes the fluidity of the liquid phase but also promotes the formation of a high-quality binder phase, thereby increasing the strength of the binder phase.

[0052] Example 10

[0053] This embodiment is exactly the same as Embodiment 8, except that the sintering temperature is increased from 1300℃ to 1350℃. The resulting sintered liquid phase has a bonding area of ​​0.62 cm². 2 The strength of the binder phase is 247 N / cm. 2 It is evident that appropriately increasing the sintering temperature can expand the liquid phase bonding range, but the bonding strength will decrease slightly.

[0054] Example 11

[0055] This embodiment is exactly the same as Embodiment 8, except that the high-temperature time is reduced from 4 minutes to 2 minutes. The resulting sintered liquid phase has a bonding area of ​​0.28 cm². 2 The strength of the binder phase is 232 N / cm. 2 It is evident that lowering the sintering temperature reduces the amount of sintering liquid phase, narrows the bonding range, and decreases the strength of the bonding phase.

Claims

1. A method for liquid-phase sintering of iron ore and strengthening of the binder phase, characterized in that: 1) The raw materials are mixed according to the proportions based on the liquid phase composition of iron ore sintering and then pressed into test blocks; 2) Place the sample block between two horizontal parallel corundum columns and heat and sinter it. After sintering, air cool it to room temperature to obtain the sample to be tested. 3) Perform destructive mechanical testing on the sample to be tested, obtain the peak mechanical strength data and the sintered phase bonding area of ​​the sample to be tested, and calculate the strength of the bonding phase in the vertical direction; 4) Place the specimen between two vertical parallel corundum pillars and repeat steps 2) and 3) to obtain the horizontal bonding phase strength; 5) Based on the vertical and horizontal liquid phase strengths, the final binder phase strength is obtained through fitting. The sintered phase is the liquid phase generated during the sintering process of iron ore and flux.

2. The method for liquid-phase sintering of iron ore and strengthening of the binder phase according to claim 1, characterized in that: The sintered phase of iron ore is mainly composed of the -3mm material in the raw material.

3. The method for liquid-phase sintering of iron ore and strengthening of the binder phase according to claim 2, characterized in that: The raw material has a particle size of <200 mesh, and the pressure range for pressing the test block is 400~450 kg / cm². 2 .

4. The method for liquid-phase sintering of iron ore and strengthening of the binder phase according to claim 1, characterized in that: The test block has a diameter of 3~15mm and a weight of 0.05~0.5g.

5. The method for liquid-phase sintering of iron ore and strengthening of the binder phase according to claim 1, characterized in that: The weight of the corundum column ranges from 5 to 60g, the size ranges from 8 to 30mm in diameter, and the height ranges from 5 to 15mm.

6. The method for liquid-phase sintering of iron ore and strengthening of the binder phase according to claim 1, characterized in that: The bonding area of ​​the sintered phase is determined by using the minimum bonding area on the two corundum pillars.

7. The method for liquid-phase sintering of iron ore and strengthening of the binder phase according to claim 1, characterized in that: The sinter mainly contains the following components by mass fraction: CaO 8~30 parts, MgO 1~4 parts, Al2O3 1~5 parts, and SiO2 2~8 parts.

8. The method for liquid-phase sintering of iron ore and strengthening of the binder phase according to claim 1, characterized in that: The heating and sintering conditions are as follows: heating rate of 5~15℃ / s, temperature of 1250~1350℃, high temperature time ≤5min, and cooling rate of 30~100℃ / min.

9. The application of the method for liquid-phase sintering of iron ore and strengthening of the binder phase according to any one of claims 1 to 8, characterized in that: It is used to quantitatively detect the strength of the bonding phase in different iron ores sintering and to analyze the bonding characteristics between mineralization domains.

Citation Information

Patent Citations

  • A method for determining the characteristic number of bond strength of sintered ore

    CN107101898B

  • Bonding strength measurement method for iron mine sintering and bonding phase

    CN110057692A

  • Method for detecting liquid phase bonding characteristic of sintered iron ores

    CN101839837A

  • Evaluation method for bonding effect of iron ore sintering liquid phase

    CN113418830A